2019
DOI: 10.1007/s13337-019-00533-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Newcastle disease virus genotype XIII with low pathogenic avian influenza exacerbates clinical outcome of Newcastle disease in vaccinated layer poultry flocks

Abstract: Background:Newcastle disease (ND) and avian influenza (AI) are infectious and economically important diseases of poultry, and multiple factors including secondary viral and bacterial infections contribute significantly in the ND/AI pathobiology. The disease pattern during co-infections of genotype XIII NDV and AI is not well understood. So far, there has been no strong explanation for such difference in mortality and severity of clinical disease. In our present case study, we describe clinico-pathological dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…However, it has been observed that ND sometimes occurred in some vaccinated poultry farms in recent years ( Mariappan et al., 2018 ; Almubarak, 2019 ). On the one hand, a few NDV strains were reported as novel subgroups and genotype mismatches ( Le et al., 2018 ; Gowthaman et al., 2019 ; Liu et al., 2019 ). On the other hand, the immune failure associated with immunosuppression caused by other viruses cannot be ignored ( Perozo et al., 2012 ; El-Aried et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been observed that ND sometimes occurred in some vaccinated poultry farms in recent years ( Mariappan et al., 2018 ; Almubarak, 2019 ). On the one hand, a few NDV strains were reported as novel subgroups and genotype mismatches ( Le et al., 2018 ; Gowthaman et al., 2019 ; Liu et al., 2019 ). On the other hand, the immune failure associated with immunosuppression caused by other viruses cannot be ignored ( Perozo et al., 2012 ; El-Aried et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent production losses, even with a good biosecurity practice, vaccination has become an increasingly important routine in the poultry industry ( Bello et al., 2018 ). However, sometimes, vaccination might not effectively reduce virus transmission and disease occurrence ( Le et al., 2018 ; Gowthaman et al., 2019 ). There are many factors that play vital roles including immunosuppressive agents, virus variation, biosecurity breaks, inadequate management practices, and harsh environments, among which immunosuppression induced by other viruses could be a possible reason ( Hoerr, 2010 ; Perozo et al., 2012 ; El-Aried et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of virulent NDV after intensive vaccination is a recurrent phenomenon in endemic countries of Asia, Africa, and Central America (6,(30)(31)(32), which is probably due to selection of virulent NDV in the face of immune pressure from vaccination (11). It also suggests that vaccination may stop active disease manifestation and protect the flock from an outbreak situation but may not stop shedding of the virus.…”
Section: F Gene Rrt-pcrmentioning
confidence: 99%
“…Usaha unggas petelur memiliki ketertarikan tersendiri karena mampu menghasilkan keuntungan yang layak dan menghasilkan produk yang dibutuhkan oleh manusia (Afandi et al, 2019). Namun, peternakan unggas petelur memiliki kendala yaitu maraknya berbagai penyakit infeksi yang bersifat kontagius, yang disebabkan oleh virus, bakteri, fungi dan riketsia ( Brown Jordan et al, 2018;Gowthaman et al, 2019). Penyakit akibat virus pada unggas petelur utama disebabkan oleh famili Avian paramyxoviridae termasuk infeksi Egg Drop Syndrome Virus (EDSV) (Kencana et al, 2017).…”
Section: Pendahuluanunclassified